Study of Voltage Sag Detection and Dual-Loop Control of Dynamic Voltage Restorer - Wang, Shuzheng; Zhang, Shaowen; Li, Xianyun (Frontiers in Energy Research, 2022)
Voltages sags have become the major issue that prevents the customers from getting high-quality power supply, and the dynamic voltage restorer (DVR) is considered an effective way to solve this issue. In this work, a method for voltage sag detection implemented in the time-domain is firstly addressed, which features highly accurate and fast response. Then, the dual-loop voltage–current control for the DVR is intensively investigated. Specifically, the optimal tuning of the inner current loop to achieve the maximum active damping is approached, and the voltage controller implemented in the discrete-time is developed. Tuning of the voltage loop based on critical damping is also approached, which features reduced settling time and avoidance of overshoot. The simulation and experimental results have verified the effectiveness of the proposed method for detection and management of voltage sags.